Subcellular localization based comparative study on radioresistant bacteria: A novel approach to mine proteins involve in radioresistance. (August 2017) - Vishambra, Divya; Srivastava, Malay; Dev, Kamal; Jaiswal, Varun
Highlights: Outer area of cell is exposed to radiation but not studied for radioresistance (RR). Diverse RR and non-RR bacteria were used for localization based comparative study. 20 uniquely conserved proteins from outer area of RR bacteria were selected. Domain, pathway and structural analysis was carried out on selected proteins. Different analysis and literature revealed the role of selected proteins in RR. Abstract: Radioresistant bacteria (RRB) are among the most radioresistant organisms and has a unique role in evolution. Along with the evolutionary role, radioresistant organisms play important role in paper industries, bioremediation, vaccine development and possibility in anti-aging and anti-cancer treatment. The study of radiation resistance in RRB was mainly focused on cytosolic mechanisms such as DNA repair mechanism, cell cleansing activity and high antioxidant activity. Although it was known that protein localized on outer areas of cell play role in resistance towards extreme condition but the mechanisms/proteins localized on the outer area of cells are not studied for radioresistance. Considering the fact that outer part of cell is more exposed to radiations and proteins present in outer area of the cell may have role in radioresistance. Localization based comparative study of proteome from RRB and non-radio resistant bacteria was carried out. In RRB 20 unique proteins have been identified. Further domain, structural, and pathway analysis of selected proteins were carried out. Out of 20 proteins, 8 proteins were direct involvement in radioresistance and literature study strengthens this, however, 1 proteins had assumed relation in radioresistance. Selected radioresistant proteins may be helpful for optimal use of RRB in industry and health care.